Conservation physiology and the COVID-19 pandemic. Issue 1 (12th January 2021) - Cooke, Steven J; Cramp, Rebecca L; Madliger, Christine L; Bergman, Jordanna N; Reeve, Connor; Rummer, Jodie L; Hultine, Kevin R; Fuller, Andrea; French, Susannah S; Franklin, Craig E
Abstract : The COVID-19 pandemic has had unanticipated effects on ecosystems and biodiversity. The conservation physiology toolbox can be used to characterize the Anthropause, mitigate the zoonotij aayc outbreaks and address the emerging issues. Conservation physiology is well positioned to deliver solutions-oriented science to guide decision makers particularly during the important post-COVID transition and economic recovery. Abstract: The COVID-19 pandemic and associated public health measures have had unanticipated effects on ecosystems and biodiversity. Conservation physiology and its mechanistic underpinnings are well positioned to generate robust data to inform the extent to which the Anthropause has benefited biodiversity through alterations in disturbance-, pollution- and climate change-related emissions. The conservation physiology toolbox includes sensitive biomarkers and tools that can be used both retroactively (e.g. to reconstruct stress in wildlife before, during and after lockdown measures) and proactively (e.g. future viral waves) to understand the physiological consequences of the pandemic. The pandemic has also created new risks to ecosystems and biodiversity through extensive use of various antimicrobial products (e.g. hand cleansers, sprays) and plastic medical waste. Conservation physiology can be used to identify regulatory thresholds for those products. Moreover, given that COVID-19 is zoonotic, there is also opportunity for conservation physiologists to work closely with experts in conservation medicine and human health on strategies that will reduce the likelihood of future pandemics (e.g. what conditions enable disease development and pathogen transfer) while embracing the One Health concept. The conservation physiology community has also been impacted directly by COVID-19 with interruptions in research, training and networking (e.g. conferences). Because this is a nascent discipline, it will be particularly important to support early career researchers and ensure that there are recruitment pathways for the next generation of conservation physiologists while creating a diverse and inclusive community. We remain hopeful for the future and in particular the ability of the conservation physiology community to deliver relevant, solutions-oriented science to guide decision makers particularly during the important post-COVID transition and economic recovery.